EMPOWERING THE ELDERLY THROUGH THE IMPLEMENTATION OF ERGONOMIC EXERCISES TO IMPROVE THE QUALITY OF LIFE - Riesmiyatiningdyah, S.Kep.Ns., M.Kes; Ninik Murtiyani (Community Service Journal of Indonesia, 2026)
The increasing number of elderly people in Indonesia is accompanied by an increasing prevalence of degenerative diseases, one of which is gout, which has an impact on reducing the quality of life. Non-pharmacological efforts such as physical activity are one effective approach in addressing this problem. This community service activity aims to improve the quality of life of the elderly through the implementation of ergonomic exercises as a non-pharmacological effort that aims to improve physical function, increase mobility, and reduce musculoskeletal complaints in a sustainable manner. This activity involved 15 elderly people. The results showed that before the intervention only 28% of elderly people were able to perform the exercise movements correctly, after the intervention there was an increase of 84% who were able to perform ergonomic exercises independently and according to procedures, the attendance rate of the elderly was 88%. Furthermore, there was a significant decrease in pain levels; specifically, the average score dropped from 6.2 (moderate category) before the intervention to 3.8 (mild category) post-intervention. Thus, ergonomic exercises are effective in improving the quality of life of the elderly.